(untitled) (Eurasian Journal of Engineering and Technology, 2024)
The article examines the tectonic deformational elements of the Darband gorge belonging to the South-Western branch of Hisar. The results of the field observation work in the Boisun uplift region of the Machai River valley are given a tariff. Attention is paid to deformation elements and kinematics of blocks of discontinuity zones, cracks. Also, the age of the rocks is determined by disjunctive and plicative deformation elements. The obtained materials testify to various mechanisms of tectonic deformations of the new era. The methods developed on the basis of the new rank analysis methodology were used for the first time in South-Western Hisar region. Tensile faults in chalk deposits in the southern part of the Darband gorge region were studied and their elements of different scales (2-3 levels) were separated. Deformation elements were studied in adjacent sections and it was determined that stress differs with deformation states